Pengaruh Leverage, Firm Size, Capital Intensity Dan Corporate Social Responsibility Terhadap Tax Avoidance (Studi Empiris Pada Perusahaan Sektor Energi yang Terdaftar di Bursa Efek Indonesia tahun 2021-2024) - Tasiya Ananda; Agus Hendrawan (CV. ITTC INDONESIA, 2026)
Tax is the main source of government revenue and plays a crucial role in supporting national development. However, differences in interests between the government as the tax authority and companies as taxpayers often lead to the practice of tax avoidance. This study aims to examine the effect of leverage, firm size, capital intensity, and corporate social responsibility (CSR) on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. This research employs a quantitative approach with an associative method. The data used are secondary data obtained from companies’ financial statements, annual reports, and sustainability reports. The sample was selected using a purposive sampling method, resulting in 36 companies with a total of 144 observations. Panel data regression analysis was conducted using EViews 13, and the best estimation model selected was the Random Effect Model (REM).The results indicate that leverage has a positive and significant effect on tax avoidance, while capital intensity has a negative and significant effect on tax avoidance. Meanwhile, firm size and CSR have no significant effect on tax avoidance. These findings suggest that higher debt utilization encourages firms to engage in tax avoidance, whereas higher capital intensity tends to reduce such practices. This study is expected to contribute empirically to the literature on tax avoidance, particularly in the energy sector, and to provide insights for policymakers and stakeholders in formulating more effective tax regulations.